Design Multistage External Gear Pumps for Dry Sump Systems: Methodology and Application. (10th March 2021) - Guerra, Davide; Polastri, Marco; Battarra, Mattia; Suman, Alessio; Mucchi, Emiliano; Pinelli, Michele
Abstract : Thanks to their manufacturing simplicity, robustness, and consolidated design knowledge, external gear pumps are widely adopted in the automotive fields. With the purpose of leading the design procedure of these positive displacement machines, within this work, the authors integrate in a comprehensive tool the salient equations adopted for the design of the major gear pump features. The presented procedure is devoted to the design of multistage external gear pumps characterized by a singular floating driving shaft supported by fluid-dynamic journal bearings. Focusing the attention on the procedure flexibility, it has been structured in three iterative calculation phases. The core section of the methodology concerns the geometrical design of the involute gear tooth profile. It is oriented to ensure a proper volumetric displacement while complying with the space requirement and the tooth manufacturing limitations. Thus, through the analytical pressure loads estimation combined with the operational parameters, the second calculation step provides the design of the driving shaft and the relevant dimensions of the journal bearings. Finally, by means of a power loss approach, the third macrosection of the procedure leads to estimating the clearances between gear tip and housing. The potentials of the methodology are exposed by describing its applications to a case study of multistage gear pump employed in the dry sump lubrication system of an automotive heavy-duty engine. Each calculation step application is outlined with reference to the proposed analytical formulation and the results of the parameters calibration are presented. Within this context, the procedure is assessed by means of a CFD analysis. The results highlight the accuracy of the methodology on the estimation of the required delivery flow rate. Aside from being accurate, flexible, and reliable, the procedure stands out for being an innovative tool within the multistage gear pump framework.